Análise da resposta inflamatória em camundongos com deficiência colinérgica em longo prazo - Santos, Paula Cassanelli [UNIFESP] (2017)
The cholinergic anti-inflammatory system has been studied in several diseases and has been shown to break in this way worsen the inflammation of the organism. A cholinergic deficiency caused by the reduction in the expression of the acetylcholine vesicular carrier protein (VAChT), responsible for the transport of acetylcholine (ACh) into the vesicles, is closely related to the reduction of ACh release. Our group recently demonstrated that animals with VAChT reduction had pulmonary inflammation in mice at 3 months of age. For more than 12 months, the age corresponding to the onset of senility and that there is a greater possibility of pulmonary injury. Objective: compare pulmonary inflammation induced by VAChT reduction in animals at 3 months and 12 months of age. Materials and Methods: They were allowed with 3 and 12 months old wild or mutants for VAChT. The animals were weighed and subjected to the Wire Hang test. After anesthesia, bronchoalveolar lavage (BAL) was removed for quantification of cells and cytokines. Empu, blood, lung, spleen, thymus and uterus were collected for further analysis. Cells were also quantified in the bone marrow and cytokine levels in the spleen, in addition to the level of estrogen in the blood and nitrite and nitrate in the lung. The data were statistically analyzed by the Sigma Statistics program and significant material for a <0.05. Results: All animals with VAChT reduction had a reduction in their class time (P <0.001) and body mass (P <0.01) in relation to their wild-type controls. Still, the wild animals with 12 months had a reduction in the time of support in the note in relation to the wild ones with 3 months (P≤0.001). The mutant animals showed a decrease in total cells in the bone marrow (P <0.05), increased total number of cells without BAL (P <0.05), and eosinophils (P <0.05). levels of TNF-α, IL-6, IL-8 and IL-1β (P <0.01) and collagen fiber deposition at 3 months compared to wild animals of the same age. At 12 months, as non-lung cells and cytokines as reductions in mutants (P <0.05) and there is no change in collagen fiber deposition in the lung compared to that observed in 3-month mutants. A percentage of thymus mass was reduced only in mutant animals at 12 months versus wild at 3 months (P <0.05) and there was no difference in spleen mass between groups. However, at 3 months, the mutants increased IL-1b, IL-8 and TNF-, a response that was not observed at 12 months. In both wild and mutant 12 month animals, reduction of the uterine mass percentage (P <0.05), without, however, the levels of estrogen in the blood. Finally, at 3 months there was an increase in non-lung nitrite / nitrate of the mutant animals, a fact that was not observed at 12 months. Conclusion: Our data demonstrate that the cholinergic system modulates pulmonary inflammation in young animals. Although VAChT-deficient animals maintain the phenotype over the long term, inflammation and oxidative stress in the lung appear to be controlled over time. The exact mechanisms of this adaptation have not yet been fully elucidated, but there seems to be no relation to estrogen levels.